(untitled) (Semiárida, 2020)
Campos biome includes regions of Paraguay, Brazil, Argentina and all Uruguay, contributing to landscapes’ beauty and mainly economy of these regions due to diversity of species that proportionates an economical and sustainable balance. In this sense knowledge about floristic diversity proportionates comprehension of biome organization, allowing to plan adequate management for a sustainable and economic development. In 2012 cool season, a botanical survey was held, using Botanal procedure, at a site nominated Rincão do 28, located at Alegrete, Rio Grande do Sul, at Brazil’s Pampa biome. 48 species were registered in the survey, mainly grasses and legumes, with 17 and six species, respectively. Andropogon lateralis was dominant among grasses and Aeschinomene falcata among legumes. Forage masses had higher contribution of two grasses: Andropogon lateralis and Paspalum notatum, both contributing with 70,4 %, the reminder were composed by 46 different species.